Community Personal Hygiene Knowledge and Attitude to Covid-19 Prevention Behavior - Nopia Wati; Oktarianita Oktarianita; Andry Sartika (Disease Prevention and Public Health Journal, 2023)
Background: The rise of Covid-19 cases has become a global issue. The government has issued guidelines for the public to reduce exposure and spread of disease or infection through personal hygiene. The purpose of this study is to ascertain community knowledge and attitudes toward personal hygiene in preventing Covid-19 in Bengkulu City. Method: This research method uses a quantitative approach. This type of research is an observational study with a cross-sectional approach. The sample in this quantitative study was taken using a simple random technique. Based on the calculation of the sample, the minimum sample size is 100 people. Data was collected by distributing questionnaires, univariate and bivariate analyses were performed. Results: The results were there was a significant association between personal hygiene knowledge toward Covid-19 prevention behaviors in Bengkulu City (p<0.05; OR= 2.6; CI 95%= 1.137-5.951). Knowledge is the collection of information about the occurrence and prevention of Covid-19, understood and acquired from the learning process throughout life, in which there are significant associations. In Bengkulu City, there was a significant association between people's attitudes toward personal hygiene and the prevention of Covid-19 (p<0.05; OR= 2.658; CI 95%= 1.184-5.969). Attitude is one of the factors that determine a person's actions in maintaining individual and group good in preventing disease. Conclusion: The results show that personal hygiene knowledge and attitudes are significantly associated with Covid-19 prevention behaviors.